STUDY ON PHARMACOKINETICS AND EFFECT ON PULMONARY FUNCTION OF HN-078 IN PEDIATRIC BRONCHIAL ASTHMA - UCHIYAMA, Hiroyuki; IIKURA, Yoji; ISHIZU, Hiroko; EBISAWA, Motohiro; KABAYAMA, Hirohiko; YAGI, Koichi; MIURA, Katsushi; AKIMOTO, Kenichi; TSUBAKI, Toshihiko; SAITO, Hirohisa; SAKAGUCHI, Naoya (Japanese Journal of National Medical Services, 1994)
The pharmacokinetics and effect on pulmonary function of HN-078, a patch formulation of tulobuterol, β2-adrenoceptor agonist, were investigated transdermally in asthmatic children. HN-078 was applied on the chests of 6 subjects previously diagnosed as having bronchial asthma. Subjects weighting from 15 to under 30kg received 1mg of tulobuterol while subjects weighing above 30kg received 2mg. Levels of serum tulobuterol and PEF values were determined before and after application. Cmax was determined to be 1.33ng/ml; Tmax was 14.0hr, and AUC0-t was 27.1ng·hr/ml. These parameters per body surface area of children were nearly equivalent to those of adults. PEF values obtained at 6: 00 AM significantly increased after patch applications; before:178.3±13.2 l/min, after: 233.3±24.0 l/min. No significant change were observed in heart rate or blood pressure, and no side-effects were found. In conclusion, it can be expected that HN-078 is useful in the treatment of pediatric bronchiral asthma.